STRATEGI GURU AKUNTANSI DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DI SMK NEGERI 3 SURAKARTA (STUDI NARATIF) - Putri Nur Windasari; Sudiyanto Sudiyanto (Universitas Sebelas Maret, 2025)
AbstractThis research aims to describe the strategies of accounting teachers in implementing the Independent Curriculum at SMK Negeri 3 Surakarta. Using a narrative qualitative method, data were collected through interviews, observations, and documents from six accounting teachers. The results show that teachers became familiar with the Independent Curriculum through seminars, workshops, the Merdeka Mengajar platform, and learning communities. Learning planning involves analyzing core competencies, formulating learning objectives and assessment plans, as well as developing teaching modules and differentiated assessments. The implementation of learning is student-centered, utilizes technology, and is collaborative in nature. Evaluation is conducted through formative and summative assessments, as well as reflections from both students and teachers. Despite facing challenges such as adapting to the concepts, time constraints, and technical issues, teachers demonstrated high initiative and adaptability.Keywords: Teacher Strategies, Independent CurriculumAbstrakPenelitian ini bertujuan mendeskripsikan strategi guru akuntansi dalam mengimplementasikan Kurikulum Merdeka di SMK Negeri 3 Surakarta. Menggunakan metode kualitatif naratif, data dikumpulkan melalui wawancara, observasi, dan dokumen dari enam guru akuntansi. Hasil penelitian menunjukkan bahwa guru mengenal Kurikulum Merdeka melalui seminar, workshop, Platform Merdeka Mengajar, dan Komunitas Belajar. Perencanaan pembelajaran melibatkan analisis CP, perumusan TP dan ATP, serta penyusunan modul ajar dan asesmen berdiferensiasi. Pelaksanaan pembelajaran berpusat pada siswa, memanfaatkan teknologi, dan bersifat kolaboratif. Evaluasi dilakukan melalui asesmen formatif dan sumatif, serta refleksi siswa dan guru. Meskipun menghadapi tantangan seperti adaptasi konsep, keterbatasan waktu, dan kendala teknis, guru menunjukkan inisiatif dan adaptasi yang tinggi.Kata Kunci: Strategi Guru, Kurikulum Merdeka